Short-term efficacy of mandibular advancement splint in treatment of obstructive sleep apnea-hypopnea syndrome - Calliandra Moura Pereira de Lima; Laurindo Zanco Furquim; Adilson Luiz Ramos (Dental Press Editora, 2013)
OBJECTIVE: The aim of the present study was to determine the short-term efficacy of treatment for snoring and obstructive sleep apnea-hypopnea syndrome (OSAHS) using a mandibular advancement splint. METHODS: The sample comprised 20 patients (13 men and 7 women; mean age = 48 years; mean body mass index = 27.07) with OSAHS. Polysomnograms were performed before and 60 days after mandibular advancement splint therapy. RESULTS: There was a significant reduction in the apnea-hypopnea index (AHI) following treatment (mean pretreatment AHI = 20.89 ± 17.9 versus mean posttreatment AHI = 4.43 ± 3.09) (p < 0.05). The snoring reduced and the sleep efficiency improved, as registered by polysomnograms (p<0.05). CONCLUSIONS: The sleep quality improved in patients using mandibular advancement splint. Further studies evaluating long-term effects are needed.